For better or worse? How more flexibility in working time arrangements and fatherhood affect men's working hours in Germany - Susanne Wanger; Ines Zapf (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2018)
Many fathers want to spend more time with their children and engage in household, but most of them continue to work full-time after the birth of a child. To better combine work and family, flexible working time arrangements might play a crucial role for fathers. Using data from the German Socio-Economic Panel and fixed-effects regression models, we investigate the impact of flexible working time arrangements on actual working hours of men and fathers. A change from fixed to flexible arrangements is associated with an increase in working hours, but it is smaller for fathers than for non-fathers. Becoming a parent and changing into flexitime or self-determined working hours within the same year is associated with a short-term decrease in working hours. The study shows that employee-oriented working time arrangements help fathers to better combine work and family, but the decrease in working hours is still small. – – Obwohl Väter zunehmend mehr Zeit mit ihren Kindern verbringen und familiäre Aufgaben übernehmen möchten, arbeitet der Großteil nach der Geburt eines Kindes weiterhin in Vollzeit. Flexible Arbeitszeitmodelle könnten hierbei eine wichtige Rolle spielen, um Beruf und Familie bei Vätern besser zu vereinbaren. Auf Basis von Daten des Sozio-ökonomischen Panels und mit Fixed-Effects-Regressionsmodellen untersu-chen wir, inwieweit sich flexible Arbeitszeitmodelle auf die tatsächlich geleisteten Arbeitsstunden von Männern und Vätern auswirken. Die Ergebnisse zeigen, dass bei einem Wechsel von festen zu flexiblen Arbeitszeitmodellen die Arbeitszeit von Männern zunächst ansteigt. Dieser Anstieg ist für Männer mit Kindern geringer als für kinderlose Männer. Wird ein Mann Vater und wechselt im gleichen Jahr zu Gleitzeit mit Arbeitszeitkonto oder selbstbestimmten Arbeitszeiten, dann reduziert sich die tatsächliche Arbeitszeit kurzfristig. Die vorliegende Studie zeigt, dass arbeitnehmerorientierte Arbeitszeitmodelle dazu beitragen können, die Vereinbarkeit von Beruf und Familie bei Vätern zu verbessern, auch wenn der Rückgang der Arbeitszeit bei Vätern noch relativ klein ist.
Keywords: J22; J81; 330; working time arrangements; working-time flexibility; self-determined working hours; flexitime within a working hours account; fatherhood; actual working hours; schedule control